CORPORATE ENTREPRENEURSHIP RESPONSIBILITY (CER) IMPLEMENTATION IN THE LIGHT OF ZAIN JORDAN - Hammoudeh, Majd; Benedek, Andrea SZABÓ (PEOPLE: International Journal of Social Sciences, 2019)
Generating new ideas, approaches, and models in social sciences- and all sciences- is essential for the world’s sustainability and development. Corporate Entrepreneurship Responsibility (CER) is a newly introduced tool in the Middle East and North Africa (MENA) region towards building region-wide entrepreneurship ecosystems. In this research, we are aiming to study the CER in-depth through a qualitative case study of a telecommunication company in Jordan, Zain Jordan, which established a division solely dedicated to the support and development of promising entrepreneurs in the county. To answer the research questions which focus on defining the CER for companies, present a strategy for the implementation of CER along with understanding the impact on the entrepreneurial society from establishing such concept or department in a company, and test whether CER could be considered part of the Corporate Social Responsibility (CSR) in a company; interviews were conducted with professionals from the CER and CSR departments at Zain Jordan, in addition to a random sample of the entrepreneurs who have been benefiting from CER division’s services. Also, analysis of the company’s reports was part of the research paper’s methodology. As a result, capital and investment, as thought by many to be the basic step of establishing and growing a business, were not considered as such. Three main factors for sustaining and growing a start-up business have been discussed: fully equipped workspace, mentorship programs, and a base of networks for the entrepreneurs. Hence, this research is a contribution to present a newly adopted business approach to support entrepreneurs and young businesses in a developing country.